2022
DOI: 10.1186/s40352-022-00195-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing community integration after incarceration: findings from a prospective study of an intensive peer support intervention for veterans with an historical comparison group

Abstract: Background The transition to the community after incarceration presents challenges for returning citizens, including the immediate need to secure housing, employment, and income. Additionally, health care is essential for this population due to high rates of chronic physical health and mental health problems and substance use disorders. There is growing recognition of the need for interventions that support returning citizens as they navigate community reintegration while simultaneously tending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Increasing access to basic needs such as housing, employment, and medical care, as well as being surrounding by a supportive and understanding community or having a relationship with a peer, have been shown in several studies to increase linkage to care, mobilize communities to advocate for systemic change, and prevent disease to create healthier populations ( A Compendium of Proven Community-Based Prevention Programs , 2013; Chutuape et al, 2010 ; McLeod et al, 2020 ). Additionally, providing access to harm reduction programs, peers, and supplies (i.e., Narcan, testing strips), can decrease negative health outcomes such as overdose and disease transmission, bridge the gap for other essential services such as housing and health care, and can be a patient-centered and individualized approach to increase linkage to health care and decrease recidivism (Ashford et al, 2018 ; Barocas et al, 2015 ; Hunter et al, 2016 ; Hyde et al, 2022 ; Khan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing access to basic needs such as housing, employment, and medical care, as well as being surrounding by a supportive and understanding community or having a relationship with a peer, have been shown in several studies to increase linkage to care, mobilize communities to advocate for systemic change, and prevent disease to create healthier populations ( A Compendium of Proven Community-Based Prevention Programs , 2013; Chutuape et al, 2010 ; McLeod et al, 2020 ). Additionally, providing access to harm reduction programs, peers, and supplies (i.e., Narcan, testing strips), can decrease negative health outcomes such as overdose and disease transmission, bridge the gap for other essential services such as housing and health care, and can be a patient-centered and individualized approach to increase linkage to health care and decrease recidivism (Ashford et al, 2018 ; Barocas et al, 2015 ; Hunter et al, 2016 ; Hyde et al, 2022 ; Khan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of peer-led programs have identified that once program expansion occurs to more standardized organizational environments, the guiding principles and values of peer-led organizations can become more and more difficult to maintain [ 49 ]. This does not preclude health and justice systems from establishing or expanding peer-led services or incorporating peer experiential workers into existing programs, as there are undoubtedly benefits in these models, as demonstrated by prior studies [ 4 ]. This does however highlight a gap filled by UTGSS, who provide a peer-led service, where the direction of service provision remains independent of the directives of health and justice organizations.…”
Section: Discussionmentioning
confidence: 99%
“…People who have been incarcerated face a number of barriers transitioning from prison back to community [ 1 3 ]. These are driven in part by the significant interruptions to community, health system, family, and peer networks of support posed by periods of incarceration [ 3 , 4 ]. Upon return to community, the most immediate needs facing this population are income and social support to obtain basic needs, including access to food, clothing, and safe and stable housing [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most persons incarcerated in the United States spend short periods (<30 days) in jail ( 27 ) and often cycle multiple times from jail to community, further fragmenting needed care. People leaving jail and prison face barriers getting Medicaid reactivated, making appointments, and getting medications ( 28 , 29 ). Another barrier, with its own set of challenges, is data sharing between correctional and community healthcare systems ( 30 ).…”
Section: Barriers To Care Created By the Miepmentioning
confidence: 99%